α2-Chimaerin Is Required for Eph Receptor-Class-Specific Spinal Motor Axon Guidance and Coordinate Activation of Antagonistic Muscles - Kao, Tzu-Jen (J Neurosci, 2015)
Axonal guidance involves extrinsic molecular cues that bind growth cone receptors and signal to the cytoskeleton through divergent pathways. Some signaling intermediates are deployed downstream of molecularly distinct axon guidance receptor families, but the scope of this overlap is unclear, as is the impact of embryonic axon guidance fidelity on adult nervous system function. Here, we demonstrate that the Rho-GTPase-activating protein α2-chimaerin is specifically required for EphA and not EphB receptor signaling in mouse and chick spinal motor axons. Reflecting this specificity, the loss of α2-chimaerin function disrupts the limb trajectory of extensor-muscle-innervating motor axons the guidance of which depends on EphA signaling. These embryonic defects affect coordinated contraction of antagonistic flexor-extensor muscles in the adult, indicating that accurate embryonic motor axon guidance is critical for optimal neuromuscular function. Together, our observations provide the first functional evidence of an Eph receptor-class-specific intracellular signaling protein that is required for appropriate neuromuscular connectivity.